The Computer Misuse (Amendment) Act 2022: Impact on Digital Journalism Practices: A Case Study of Uganda Christian University - Ronald Ocweo (Uganda Christian University)
This study Assesses the Impact of the Computer Misuse (Amendment Act) 2022 on the practice of digital journalism a case study of Uganda Christian University. This study seeks to establish the loopholes within the Computer Misuse (Amendment Act) 2022 which are liable for exploitation by narrow interest groups, it further addresses how these loopholes have hindered the advancement of digital journalism and how the loopholes found can be bridged. The study employs qualitative methods, including questionnaires, and content analysis, to assess the impact of the Computer Misuse (Amendment Act) 2022 on digital journalism practices. This study contributes to the existing literature on digital journalism by establishing their channels or mode of operation in the digital world, it further elaborates in-depth on the origins and provisions of the Computer Misuse (Amendment Act) 2022. Using a theoretical framework based on Authoritative theory, the study assesses how the Act is a tool for the suppression of digital press freedom in their quest to collect, gather, produce, and share content online. It also highlights the significance of media freedom in a bid for nation-building, accountability, and having an informed society.
Undergraduate Research